The potential for using metagreywacke to study metamorphism of amphibolite facies conditions: a comparison study within the Luminárias Nappe, Southern Brasília Orogen (Southeastern Brazil) - Fumes, Regiane A. [UNESP]; Luvizotto, George L. [UNESP]; Moraes, Renato; Patto, Lara A. [UNESP] (Springer Nature, 2021)
Metagreywacke is a very common rock type in orogenic settings. It occurs in several domains within the Neoproterozoic Southern Brasília Orogen, that registers convergent events related to the Western Gondwana formation. Studied rocks derive from the Luminárias Nappe, which is composed of metapelite (Campestre Unit), quartzite and metagreywacke (Santo Antônio Unit) that occur in the northern portion of the structure. The potential use of the metagreywacke in metamorphic studies and the metamorphic P–T path of the Santo Antônio Unit was constrained using isochemical phase diagram, quantitative compositional mapping, and composition mineral contours. The metamorphic peak mineral assemblage of the metagreywacke is biotite + plagioclase + garnet + muscovite + ilmenite + quartz. Rutile is a prograde phase, but is replaced by ilmenite at metamorphic peak, while chlorite is a retrograde phase, as it replaced biotite and garnet. The garnet is almandine rich, preserves zoning, with lower almandine and pyrope contents in the core and lower spessartine and grossular contents in the rim. The peak assemblage is stable at temperatures of 570 ˚C to 650 ˚C and pressures of 0.7 GPa to 1.05 GPa. Prograde conditions of 540 ˚C and 0.9 GPa are obtained using the garnet core spessartine composition and the rutile occurrence. The compositional mineral contours of garnet rim, combined with those of muscovite and plagioclase, intercept at 630 ˚C and 1.0 GPa and indicate peak metamorphic conditions. Later crystallization of chlorite took place during retrograde conditions at 580 ˚C and 0.7 GPa, defining a single clockwise P–T path. The calculated topology of metagreywacke pseudosection, in this study, resembles those of a typical metapelite, and the crystallization sequence of metamorphic index minerals, along a Barrovian gradient, with slightly distinguished mineral assemblages. The similarity and differences for the two rock types occurs, specially under amphibolite facies conditions. Therefore, the metagreywacke is a promising protolith for metamorphic studies, even if it presents marking differences from pelites. The constrained P–T path is similar to those presented in previous works carried out in the Luminárias Nappe, associated with the collisional setting in the Southern Brasília Orogen.
Keywords: Biotite schist; Carrancas Group; Metagreywacke; Perple_X; Santo Antônio Unit; XMapTools